ANALISIS PERANCANGAN LAYOUT GUDANG ADHESIVE UNTUK MENINGKATKAN KAPASITAS PENYIMPANAN MENGGUNAKAN METODE SHARED STORAGE (STUDI KASUS: PT. XYZ) - Sarlito, Setia Cahya; Miharja, Rediawan (Bisnis-Net, 2025)
This study aims to redesign the warehouse layout by implementing a shared storage method to increase storage capacity and efficiency. The adhesive warehouse faces several problems, including an inefficient layout so that there are empty areas that have not been optimally utilized. In addition, workers experience difficulties in transferring and searching for goods because the storage system used is randomized and the warehouse is overcapacity. The approach used is descriptive quantitative. The analysis method includes calculating the average incoming and outgoing goods, space requirements (space requirements), aisle width (aisle), throughput value, assignment, and delivery distance of each area (rack) to the warehouse door. The results of the study showed that the proposed layout was able to increase storage capacity from 93 pallets to 102 pallets and reduce the distance of material handling by 9.24 meters. Thus, the shared storage method is effectively applied to improve the efficiency and effectiveness of the PT. XYZ adhesive warehouse layout.